Comparative efficacy of BAU-fowl cholera and DLS-fowl cholera vaccines in indigenous chicken (Research in Agriculture Livestock and Fisheries, 2018)
The present study was conducted to determine the immune response induced in indigenous chicken produced against BAU-FC and DLS-FC vaccines with their efficacy study against Pasteurella multocida. A total of forty (40) chickens were selected and divided into Group A (15), Group B (15) and Group C (10). Group A and B were vaccinated with BAU-FCV and DLS-FCV, respectively at the dose rate of 0.5 ml through SC at six weeks of age followed by boostering at 10 weeks of age while Group C was kept as unvaccinated control. Sera samples were collected after primary and booster vaccination and antibody titre was determined by Passive hemagglutination (PHA) test. The mean PHA titres recorded at 4 weeks after primary vaccination was 51.20 ± 7.84 in birds of group A and 38.40 ± 6.40 in birds of Group B. After booster vaccination, mean PHA titer was found 140.80 ± 31.35 at 16 weeks of age in case of BAU-FC vaccinated group and 115.20 ± 12.80 in case of DLS-FC vaccinated group. The mean PHA titer was 204.80 ± 31.35 and 179.20 ± 31.35 at 19 weeks of age in birds of BAU-FC and DLS-FC vaccinated group, respectively. Birds of all groups were challenged with virulent P. multocida at 17 weeks of age. It was observed that vaccinated chickens showed maximal resistance (100%) following challenge with virulent whereas unvaccinated control birds failed to resist the challenge infection. It can be assumed from the findings of present research work that both BAU-FCV and DLS-FCV are able to protect indigenous chicken from the outbreak of avian pasteurellosis and BAU-FV vaccine showed relatively higher immuno-protective titre than that of DLS-FC vaccine.Res. Agric., Livest. Fish.5(2): 193-199, August 2018